Pengembangan LKPD Berbasis Contextual Teaching and Learning untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Pada Materi Sistem Gerak - Adella Shaharani; Kartika Manalu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop a student worksheet (Lembar Kerja Peserta Didik or LKPD) based on Contextual Teaching and Learning that is valid, practical, and effective for students. The research method employed was research and development, with instruments consisting of teacher and student needs questionnaires, material and media validation sheets, practicality sheets, as well as effectiveness sheets through pretests and posttests. Data analysis included validity, practicality, and effectiveness tests. The results indicated that the developed LKPD demonstrated high validity, was practical for both teachers and students, and was effective in enhancing students’ critical thinking skills. In conclusion, the LKPD based on Contextual Teaching and Learning can serve as appropriate teaching material to foster critical thinking skills in biology concepts. Keywords: Critical Thinking, Contextual Teaching And Learning, Development